MORPHOLOGICAL AND ANATOMICAL INVESTIGATION OF THREE SCANDIX SPECIES FROM TURKEY - Demirpolat, Azize; Dogan, Gulden; Bagci, Eyup (Bangladesh Botanical Soc, 2019)
Morphological, morphometrical and anatomical features of some Scandix species (Scandix pectenveneris, S. macrorhyncha and S. balansae) were investigated to compare and determine the taxonomic importance of these characters. Description, synonyms, Turkish names, flowering times, habitat properties and anatomical structure of each species were determined. According to morphological and anatomical characters S. macrorhyncha and S. pecten-veneris showed high-level similarity. However, endemic S. balansae showed distinct both morphological and anatomical differences from the other Scandix species.
Keywords: Scandix; Morphology; Anatomy